Developing the amazing photocatalyst of ZnAg2GeSe4, ZnAg2Ge0.93Fe0.07Se4 and ZnAg2Ge0.86Fe0.14Se4 through the computational explorations by four DFT functionals. Issue 7 (July 2021) - Kumer, Ajoy; Chakma, Unesco
Abstract: For developing the stannite type quarterly crystal photocatalyst, the electronic structure and optical properties of ZnAg2 GeSe4, ZnAg2 Ge0.93 Fe0.07 Se4 and ZnAg2 Ge0.86 Fe0.14 Se4 were calculated and compared with the parent stannite type quarterly crystal, ZnAg2 GeS4 . First of all, the four functionals, such as GGA with PBE, GGA with RPBE, GGA with WC and LDA with CA-PZ functionals were used for primary screening of electronic band structure and structural geometry for ZnAg2 GeS4 while the band gap was in 0.93, 0.97, 0.77 and 0.67 eV, respectively. It must be mentioned that the experimental value of ZnAg2 GeS4 was 0.94 eV so that the GGA with PBE showed the overlapping value of band gap. The main focus of this paper is to evaluate the band structure of newly predicted the stannite type quarterly crystal, ZnAg2 GeSe4 using four methods replacing the Sulfur atom by Serium atom on ZnAg2 GeS4 . The band gap for four methods, such as GGA with PBE, GGA with RPBE, GGA with WC and LDA with CA-PZ functionals, were calculated in 0.84 eV, 0.92 eV, 0.68 eV and 0.58 eV. Afterward, Fe atom was doped by two portions, like 7% and 14%, to make the empirical formula, ZnAg2 Ge0.93 Fe0.07 Se4 and ZnAg2 Ge0.86 Fe0.14 Se4 . The numerical values of band gaps for ZnAg2 Ge0.93 Fe0.07 Se4 and ZnAg2 Ge0.86 Fe0.14 Se4 were 0.43 eV, 0.53 eV, 0.35 eV and 0.18 eV and 0.24 eV, 0.31 eV, 0.18 eV and 0.08 eV, respectively, using the four respected DFT methods. For their contributed orbitals of each atom on crystal, the density of state and the partial density of state for ZnAg2 GeSe4, ZnAg2 Ge0.93 Fe0.07 Se4 and ZnAg2 Ge0.86 Fe0.14 Se4 crystals were simulated through the GGA with PBE method as standard regarding the calculation of band gap study comparison with experimental magnitude. For giving the further information about the nature in case of optical evidence, the six optical properties, such as absorption, reflection, refractive index, conductivity, dielectric function and loss function were calculated, and make a comparative study. In case of UV light absorption in lighten to optical parameters, the ZnAg2 Ge0.86 Fe0.14 Se4 can show the highest absorption up to convenience energy region as photocatalyst. Abstract : Band gap, Density of States, Photocatalyst, Dielectric function.